2022
DOI: 10.1093/g3journal/jkac139
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome-scale assembly with a phased sex-determining region resolves features of early Z and W chromosome differentiation in a wild octoploid strawberry

Abstract: When sex chromosomes stop recombining, they start to accumulate differences. The sex-limited chromosome (Y or W) especially is expected to degenerate via the loss of nucleotide sequence and the accumulation of repetitive sequences. However, how early signs of degeneration can be detected in a new sex chromosome is still unclear. The sex determining region (SDR) of the octoploid strawberries is young, small, and dynamic. Using PacBio HiFi reads, we obtained a chromosome scale assembly of a female (ZW) Fragaria … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 112 publications
1
13
0
Order By: Relevance
“…In particular, 'Florida Brilliance' sub-genome A showed higher sequence similarity with F. vesca than other sub-genomes, which agrees with Hardigan et al (5). Translocations on 3C, 4A, 4B and 4C were apparent when comparing with the genome of F. chiloensis (Figure 3D) (10). The genetic positions from a 'Florida Brilliance' linkage map and physical coordinates of SNPs showed good collinearity (Figure 4).…”
Section: Phased Octoploid Genome Assemblysupporting
confidence: 85%
See 3 more Smart Citations
“…In particular, 'Florida Brilliance' sub-genome A showed higher sequence similarity with F. vesca than other sub-genomes, which agrees with Hardigan et al (5). Translocations on 3C, 4A, 4B and 4C were apparent when comparing with the genome of F. chiloensis (Figure 3D) (10). The genetic positions from a 'Florida Brilliance' linkage map and physical coordinates of SNPs showed good collinearity (Figure 4).…”
Section: Phased Octoploid Genome Assemblysupporting
confidence: 85%
“…Translocations on 3C, 4A, 4B and 4C were apparent when comparing with the genome of F . chiloensis (Figure 3D) (10). The genetic positions from a ‘Florida Brilliance’ linkage map and physical coordinates of SNPs showed good collinearity (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Gates (1926) and Wright et al (2015) suggested that the multiplied sex chromosomes (Z or X) in polyploids can gradually transform into autosomes, and this appears to have occurred in polyploid Rumex acetosella, which each retained have only one pair of sex chromosomes (XY for males) (Singh, 1968;Cunado et al, 2007). The dioecious octoploid Fragaria (e.g., Fragaria chiloensis) species that arose from hermaphroditic diploid progenitors also each have only one SLR on one of the homologues in each species studied (Tennessen et al, 2016;Cauret et al, 2022), while the others may have become autosomes. The "new" autosomes could still be just like the ancestral X or Z chromosome, or their genes might be lost due to diploidization.…”
Section: Cytological Mechanismsmentioning
confidence: 99%